The Role of Small Projects in Achieving Sustainable Development in Iraq (2003-2021) (Czech Journal of Multidisciplinary Innovations, 2025)
The goal of this research is to look at the reality of small enterprises in Iraq from 2003 to 2021 and illustrate how they help the economy expand and reach goals for sustainable development. The research is based on the premise that, under optimal circumstances, small enterprises— despite little finance and insufficient institutional backing—constitute a crucial basis for addressing unemployment and fostering regional manufacturing. The quantitative study of official data from the right Iraqi authorities included the number of firms, the number of workers in those businesses, and an estimate of how much they contributed to the GDP. The results revealed that there was a close link between the sector's GDP contribution and the number of workers. The highest values were in 2011 and 2012, and there was a big reduction between 2014 and 2016 because of problems with the economy and security. The research also found additional structural problems in this market, such as not enough financing, not many incubators, government rules that don't make sense, and an infrastructure that isn't very strong. Because of this, the research says that the government should make a clear national plan to help small businesses. This plan should include money for educating entrepreneurs, changes to the law, and places to borrow money. This will make it more likely that these businesses will be able to hire people and make things, changing them from one-time initiatives into effective tools for achieving long-term growth and economic stability